KARAKTERISTIK KADER POSYANDU DALAM PENGGUNAAN PEDOMAN GIZI SEIMBANG (PGS) MELALUI PENDEKATAN PROBLEM BASED DI WILAYAH KERJA PUSKESMAS PACERAKKANG DAYA MAKASSAR - Hendrayati Hendrayati; Sitti Saharia Rowa; Nursalim Nursalim (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
ABSTRAKThe government issued a Balanced Nutrition Guidelines (BNG) starting in 2014, with the aim of being used as a guideline in the administration of meals starting at the family and national level. The application of BNG to date has not been evenly distributed, especially for housewives who are not working, poor and have low education. In housewives like this usually children under five years old are obtained with nutritional problems both under nutrition and stunting. The use of posyandu cadres as a facilitator for local communities is expected to be able to transfer knowledge well because it is supported by factors of closeness and good emotional ties with housewives around their homes.This research is a study that measures the knowledge, attitudes and skills of posyandu cadres in implementing PGS. Materials in improving the indicators are used by the BNG module. Measurements are carried out 2 times. Research result provide an illustration that there is an increase in knowledge about the use of PGS twice as much and change in knowledge by 32%. Attitude changes increased 16% and skills change reached 48%.